2019
DOI: 10.1016/j.fuel.2018.08.152
|View full text |Cite
|
Sign up to set email alerts
|

Study of CO2 removal in natural gas process using mixture of ionic liquid and MEA through process simulation

Abstract: There has been a shift to less carbon intensive fuels such as natural gas to meet energy demand due to increasing pressure to cut CO2 emissions. This has prompted a need to assess unconventional and contaminated natural gas reserves (which contains CO2 concentration of 20mol% or more). The CO2 capture process with MEA as the solvent is mostly adopted to treat contaminated natural gas. In this study, the option of using a blend of ionic liquids (IL) and MEA as a promising solvent in the process was investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 41 publications
0
25
0
3
Order By: Relevance
“…Gas alam memiliki beberapa gas pengotor diantaranya CO2, H2S dan merkaptan. Gas alam mentah mengandung CO2 sekitar 20%-mol yang membuat gas alam tidak ekonomis [8]. Gas CO2 tidak diinginkan karena mengandung racun pada katalis untuk sintesis amoniak dan metanol, mengurangi nilai bakar dari gas alam serta dapat menjadi padat (icing) saat proses pencairan gas alam [3].…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Gas alam memiliki beberapa gas pengotor diantaranya CO2, H2S dan merkaptan. Gas alam mentah mengandung CO2 sekitar 20%-mol yang membuat gas alam tidak ekonomis [8]. Gas CO2 tidak diinginkan karena mengandung racun pada katalis untuk sintesis amoniak dan metanol, mengurangi nilai bakar dari gas alam serta dapat menjadi padat (icing) saat proses pencairan gas alam [3].…”
Section: Pendahuluanunclassified
“…Gas CO2 tidak diinginkan karena mengandung racun pada katalis untuk sintesis amoniak dan metanol, mengurangi nilai bakar dari gas alam serta dapat menjadi padat (icing) saat proses pencairan gas alam [3]. Berbagai teknologi pemisahan CO2 dari gas alam seperti absorpsi fisik dan kimia, pemisahan kriogenik dan pemisahan membran dilakukan agar dapat memenuhi kriteria transpor perpipaan dan atau proses likuifaksi untuk LNG [8].…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Borhani et al 39 verified the reliability of the rate-based model by capturing the acidic gases, CO 2 and H 2 S, in the sweet gas in two cases, which showed that there was almost no variation between the experimental and simulation results. In the CO 2 capture process of natural gas, Salvinder et al 38 and Emmanuel et al 37 adopted the rate-based model for the energy consumption and process analysis.…”
Section: Model Validationmentioning
confidence: 99%
“…New solvents that increase the CO 2 absorption and desorption of CO 2 have been developed such as the nanoparticle additives and biphasic solvents (Liu et al, 2019;Mehassouel et al, 2018;Wang et al, 2016). Despite that, aqueous solution of monoethanolamine is undoubtedly still the most extensive, mature, appropriate, and well-documented chemical solvent for the CO 2 capture in post-combustion processes (Akinola et al, 2019;Ali Saleh Bairq et al, 2019;Gheni et al, 2018;Mohammadpour et al, 2019;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%